Analytical review on potential use of waste engine oil in asphalt and pavement engineering - Zahraa, Jwaida; Anmar, Dulaimi; Alireza, Bahrami; Md Azree Othuman, Mydin; Özkılıç, Yasin Onuralp; Putra Jaya, Ramadhansyah; Wang, Yuexin (Elsevier Ltd, 2024)
This article provides a comprehensive overview of the research utilising waste engine oil (WEO) in asphalt binders for multiple application purposes and the economic and environmental implications. It covers the various types and sources of WEO for information on their characteristics and the process of preparing WEO-asphalt binders. The study collects the effects of WEO in different applications, including asphalt modification, aged asphalt rejuvenation, self-healing asphalt agents, and WEO composites. It also discusses works on the economic and environmental appraisal associated with a wide WEO utilisation. WEO exhibits both positive and negative influences on asphalt properties. Generally, it improves the performance of asphalt at low temperatures, specifically in terms of reducing issues like thermal cracking and enhancing fatigue resistance. However, it may have a negative impact on the performance of modified asphalt binders at high temperatures. WEO, due to its high concentration of light components, improves the overall performance of aged asphalt. The integration of WEO and reclaimed asphalt binders can enhance the crack resistance, which however highly relies on the added WEO quantity. Future research should be prioritised to understand the comprehensive impact of WEO on reclaimed asphalt binders for the compatibility between the rejuvenator compound and reclaimed aged asphalt, and the effect of WEO on the durability of modified asphalt mixes. In addition, field investigations and analyses are required for a bigger, inclusive, and more detailed picture of the economic and environmental impacts.